2020
DOI: 10.1152/ajpheart.00024.2020
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 during childhood is associated with microvascular function later in life

Abstract: With a longitudinal cohort, novel observations from the present study demonstrate that individuals who had lower Sirt1 early in life exhibit premature microvascular dysfunction during adulthood and may be at higher risk to develop CVD. These results provide experimental evidence that Sirt1 may play an important role in microvascular function with age and represent a potential therapeutic target to prevent premature vascular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
2
3
0
Order By: Relevance
“…37 In humans, systemic lower circulating SIRT1 in childhood is associated with microvascular dysfunction during adulthood. 38 Our findings confirm the tight relationship between vascular SIRT1 and age-and metabolic-related microvascular endothelial function in A-D, Relaxing response to cumulative concentration to Ach in vessels precontracted with norepinephrine in the 4 groups (young nonobese: n=5; old nonobese: n=16; young obese: n=8; old obese: n=22). Vasodilatory response is expressed as % of the maximal diameter.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…37 In humans, systemic lower circulating SIRT1 in childhood is associated with microvascular dysfunction during adulthood. 38 Our findings confirm the tight relationship between vascular SIRT1 and age-and metabolic-related microvascular endothelial function in A-D, Relaxing response to cumulative concentration to Ach in vessels precontracted with norepinephrine in the 4 groups (young nonobese: n=5; old nonobese: n=16; young obese: n=8; old obese: n=22). Vasodilatory response is expressed as % of the maximal diameter.…”
Section: Discussionsupporting
confidence: 84%
“… 37 In humans, systemic lower circulating SIRT1 in childhood is associated with microvascular dysfunction during adulthood. 38 Our findings confirm the tight relationship between vascular SIRT1 and age- and metabolic-related microvascular endothelial function in humans. They promote the hypothesis of SIRT1 as a crucial biological link between cellular energy availability, metabolism, and aging.…”
Section: Discussionsupporting
confidence: 82%
“…SIRT1 are not presently clear (36), circulating SIRT1 has also been shown to predict microvascular function (23), supporting the role of SIRT1 in the pathophysiology of endothelial dysfunction and the use of circulating SIRT1 as a novel biomarker to explore this association. In the present study, whereas oxLDL concentrations were similar, circulating SIRT1 was lower in the ACE þ than ACE À group (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, SIRT1 has been shown to directly activate endothelial nitric oxide synthase (eNOS) (20) and inhibit endothelial oxidative stress (21,22). Accordingly, Rodriguez-Miguelez et al (23) recently reported that individuals with low circulating SIRT1 during childhood are more likely to exhibit premature vascular dysfunction in young adulthood. Therefore, it is plausible that aberrations in SIRT1 signaling and/or increased oxidative stress may contribute to ACEs-related impairments in vascular endothelial function (VEF).…”
Section: Introductionmentioning
confidence: 99%
“…Low SIRT1 levels early in life are associated with premature microvascular dysfunction during adulthood and increase the risk to develop CCVD. 158 Endothelial SIRT1deficient mice exhibit global endothelial dysfunction, underlying the development of microvascular and macrovascular complications. 159,160 Overexpression of SIRT1 in endothelial cells prevents age-induced impairment of vasodilator responses and inhibits vasoconstrictor responses to acetylcholine.…”
Section: Antivascular Aging Effects Of Endothelial Sirt1 Endothelial ...mentioning
confidence: 99%